Dominant Physical Condition Of Porprov Karate Athletes Forki Kapuas Kata Category - Uwais Wahyu Abdillah; Akhmad Amirudin; Ramadhan Arifin (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2025)
Physical condition is an important factor for athletes during training and competitions. This study aims to assess the physical condition of PORPROV (Provincial sports week) Kapuas athletes who compete in karate in kata category . The research uses a descriptive quantitative approach. Data was collected using physical fitness tests, including Multi-Stage Fitness Test (MFT), standing board jump, push-up test, and standing stork test. The population of this study is PORPROV (Provincial sports week)  FORKI (Federasi olahraga karate-do Indonesia) Kapuas athletes kata category which is 11 people and uses the total sampling technique which means that this study uses athletes from the entire population totaling 11 people. The findings revealed that the majority of athletes' physical condition fell into the "Enough" category in the four tests given. Based on these results, it can be concluded that the physical condition of athletes kata category is generally enough. The study can serve as a valuable evaluation tool for coaches and athletes in developing targeted physical training programs that address the key fitness components required in karate.